2014
DOI: 10.7763/ijssh.2014.v4.371
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of God Consciousness and Religiosity in Coping with Anxiety at Workplace among Malaysian Muslim Professionals

Abstract: Abstract-Anxiety is form of psychological condition that can cause serious harm to human mind and overall well being. Today's stressful and highly demanding work setting has intensified the pressure and expectations felt by the professionals in Malaysia. The intensity of stress may affect general safety, health and even lifestyles or relationships of a normally working persons. There are some people who turn to God and religion as alternative to heal or cope with their psychological discomfort. Thus, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…The term “spiritual coping” has been usually used instead of or synonymously with religious coping in the literature. 8 9 10 11 We believe that the term “spiritual coping” is not a correct expression, as spirituality is the high states, blessings, tastes, and happiness. It describes what a person feels in his conscience and soul.…”
Section: Religious Coping and Parents In The Nicumentioning
confidence: 99%
“…The term “spiritual coping” has been usually used instead of or synonymously with religious coping in the literature. 8 9 10 11 We believe that the term “spiritual coping” is not a correct expression, as spirituality is the high states, blessings, tastes, and happiness. It describes what a person feels in his conscience and soul.…”
Section: Religious Coping and Parents In The Nicumentioning
confidence: 99%
“…Religiosity is an important variable that can affect the level of stress in pregnant women. This research supports the theory of Watterson and Giesler (Radzi et al, 2014) that religious individuals have a higher level of self-control, which enables them to cope better with difficult tasks and life situations, thereby helping to prevent stress, anxiety, and depression. Additionally, high levels of religiosity have the potential to reduce stress through the emotional aspect of feeling the presence of God, as individuals feel they are not alone in facing life's challenges (Alflakseir & Coleman, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Besides, exercise during pregnancy will also increase maternal blood circulation thereby optimizing the amount of oxygen carried to the muscles and body tissues (22). Then, by doing dhikr, the human mind is directed towards remembrance to Allah and towards all the positive elements in life so that anxiety and stress can be reduced (23). Previous research showed that antenatal class using the Maryam method was more effective than the standart antenatal class in reducing anxiety levels in pregnant women (p<0.05), but further researches are still needed to explore variables that affect the level of anxiety such as levels of the hormone cortisol or β-Endorphin levels (24).…”
Section: Introductionmentioning
confidence: 99%